SDSS J211852.96-073227.5: The first non-local, interacting, late-type intermediate Seyfert galaxy with relativistic jets - Järvelä E; Berton M; Ciroi S; Congiu E; Lähteenmäki A; Di Mille F (EDP SCIENCES S A, 2022)
It has been often suggested that a tangible relation exists between relativistic jets in active galactic nuclei (AGN) and the morphology of their host galaxies. In particular, relativistic jets may commonly be related to merging events. Here we present for the first time a detailed spectroscopic and morphological analysis of a Seyfert galaxy, SDSS J211852.96-073227.5, at z=0.26. This source has previously been classified as a gamma-ray emitting narrow-line Seyfert 1 galaxy. We re-observed it with the 6.5 m Clay Telescope and these new, high-quality spectroscopic data have revealed that it is actually an intermediate-type Seyfert galaxy. Furthermore, the results of modelling the Ks-band near-infrared images obtained with the 6.5 m Baade Telescope indicate that the AGN is hosted by a late-type galaxy in an interacting system, strengthening the suggested connection between galaxy interactions and relativistic jets.